Epidemiology of human leptospirosis and molecular characterization of Leptospira spp. isolated from the environment and animal hosts in Peninsular / Benacer Douadi - Benacer , Douadi (2017)
Leptospirosis is a globally important zoonotic disease caused by spirochetes from the genus Leptospira. Transmission to humans occurs either directly from exposure to contaminated urine or infected tissues, or indirectly via contact with contaminated soil or water. In Malaysia, leptospirosis is an important emerging zoonotic disease with dramatic increase of reported cases over the last decade. However, there is a paucity of data on the epidemiology and genetic characteristics of Leptopsira in Malaysia. The first objective of this study was to provide an epidemiological description of human leptospirosis cases over a 9-year period (2004–2012) and disease relationship with meteorological, geographical, and demographical information. An upward trend of leptospirosis cases were reported between 2004 to 2012 with a total of 12,325 cases recorded. Three hundred thirty-eight deaths were reported with an overall case fatality rate of 2.74%, with higher incidence in males (9696; 78.7%) compared with female patients (2629; 21.3%). The average incidence was highest amongst Malays (10.97 per 100,000 population), followed by Indians (7.95 per 100,000 population). Stratification according to geographical distribution showed that the state of Malacca recorded the highest disease incidence average (11.12 per 100,000 population) followed by Pahang (10.08 per 100,000 population). In view of the recent rise in reported human cases, the next aim was to isolate and characterize Leptospira species from the environment (water and soils), and host reservoirs (rat, dog, cat, swine) from selected sites in different States in Malaysia. Positive isolates were obtained from urine and kidney samples of 59/167 rats, 11/50 dogs and 5/81 swine. Among 151 environmental samples collected from different sites, 35 samples (28 water, 7 soil) were positive with 8 (7 water, 1 soil) pure culture samples. Microscopic agglutination test (MAT) identified 4 Leptospira spp. serogroups (Javanica, Bataviae, Pomona and Canicola) in the zoonotic samples, while environmental samples were unidentified. Molecular characterization by PFGE showed a high diversity among the environmental isolates (8 profiles), while only 5 different patterns were generated among zoonotic and clinical isolates. RAPD-PCR using primer pairs B11 and B12 subtyped 71 isolates into 32 RAPD profiles. A Multilocus sequence typing (MLST) using 7 seven house-keeping loci generated a phylogenity tree with 7 different MLST type (STs) among the 63 isolates, however no environmental strains were typed using this scheme. Antimicrobial susceptibilty analysis showed all 65 Leptospira spp. isolated from humans (n = 1), reservoir animals (rat, n = 60; dog, n = 1; swine, n = 1) and the environment (n = 2) were resistant to trimethoprim, chloramphenicol and sulfomethaxazole. Doxycycline, ampicillin and penicillin G were only effective against the clinical and zoonotic isolates. Finally, multiplex PCR (mPCR) was developed and proved to be a promising tool for the rapid early detection and differentiation of leptospirosis from various specimens using two primer sets, LG1/LG2 for genus confirmation, which targeted the 16SrRNA gene and species identification and pathogenicty determination using LP1/LP2 primers which targeted ligB gene. These results highlight the need for close partnerships between scientists, clinicians, veterinarians and public health officers in order to reduce the disease burden.